(3ZQjH GdbQBfs - (3CHh HcQ eMeO Hf YRjR GdSLSJGfjs
(3ChdgG (B:s
(3gPG JaSjQ ZQjH GdbQBf Cda Ydi MQha GdeYLe djbQH JfGhdg hjSgd MaXg Ydi ef CQGOg hHGddg GdJhajb GdgeRI GdeaJhMI Cde hSGFQ MQha GdgLGA ai ChGFd GdShQ s
(3BNQgG (B:s
(3HHGH GdecShQI bjd djS ai cdGe GdYQH cdeI ChdgG jGA ecShQI EdG bhdge jSGQ hjSGQ dGHO hGddg CYde Je GdcJGH HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3bhHdJ SfI (B594(3g` hUMMJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1208s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(345) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs